P07.18 Ease and comfort of a novel herswabtm vaginal self-sampling device for the detection of sexually transmitted infections. (13th September 2015) - Chernesky, M; Arias, M; Jang, D; Gilchrist, J; Li, J; Smieja, M
Abstract : Introduction: Eve Medical Inc. (Toronto, Canada) has developed a novel HerSwab TM device for self-collection of vaginal samples for STI screening. The objective of this study was to survey opinions on ease and comfort from women using the HerSwab TM . Methods: A total of 189 women with infection prevalence of 10.6% for C. trachomatis and 2.6% for N. gonorrhoeae by Aptima Combo 2 assay testing signed consent for a physician-collected sample with a vaginal swab and a self-obtained vaginal sample using the HerSwab TM device. The order of collection was randomised. A research coordinator demonstrated steps for proper self-sampling following instructions in the HerSwab TM package. Following self-collection, each participant completed a 5-point Likert Scale questionnaire indicating ease (5 steps) and comfort (3 steps) of self-collection. Additional questions included: whether the instructions were easy to follow; whether there was anything that participants would change about the device; whether participants preferred physician or self-collection and why; and whether participants would consider self-sampling at home. Results: The majority of women experienced high levels of ease and comfort. Instructions were easy to follow for 97.1% (169/175); 80.9% (140/173) preferred self-collection over physician-collection; and 79.7% (137/172) would consider self-collection at home. Reasons for preferring self-collection included convenience, privacy, confidentiality, an opportunity for self-education of own body, greater access for people with disabilities, comfort, and a reduction of physical and psychological stress. Suggestions to improve ease and comfort included making the brush bristles softer and including arrows on the handle of the device to better indicate the direction of turning. Conclusion: Vaginal self-sampling with the HerSwab TM device demonstrated high levels of ease and comfort. The majority of women found the instructions easy to follow, preferred self-sampling over physician sampling and would consider self-collection at home. Organisers of STI screening programs should benefit from this personal feedback on vaginal self-collection. Disclosure of interest statement: Dr. Chernesky has received research funding from Eve Medical Inc.